(untitled) (Journal of Renal and Hepatic Disorders, 2023)
Patients with type 2 diabetes mellitus (T2DM) may have renal involvement because of isolated diabetic nephropathy (DN), isolated non-diabetic renal disease (NDRD), or mixed lesions (DN combined with NDRD). This study was conducted to find out incidence, histopathological pattern, and clinical predictors of NDRD in the Kashmiri population. This is a single-center prospective observational study conducted from August 2015 to July 2017. Patients with T2DM presenting with atypical clinical features of renal involvement underwent kidney biopsy. A total of 33 patients were included. Isolated NDRD was found in 16/33 (48.5%) patients, isolated DN was discovered in 10/33 (30.3%), and mixed lesions in 7/33 (21.2%) patients. NDRD with or without DN was present in 23/33 (69.7%) patients. Overall, the most common renal histopathological lesion in NDRD was immunoglobulin A (IgA) nephropathy present in 7/23 (30.4%) patients. In mixed lesions, FSGS and TMA were the most common renal lesions present in 2/7 (28.57%) patients. The mean duration of diabetes in NDRD and isolated DN groups was 4.4±3.6 and 7.0±2.9 years, respectively (P = 0.04). NDRD was present in 21/23 (91.3%) patients without diabetic retinopathy (P = 0.016). Our data demonstrated that more than half of the patients with T2DM with atypical features had NDRD upon renal biopsy. The absence of diabetic retinopathy and a shorter duration of diabetes were indicators of NDRD. IgA nephropathy was the most prevalent renal pathology. Clinicians must consider kidney biopsy liberally, especially in patients with unclear etiology of a kidney disease. Patients with type 2 diabetes mellitus (T2DM) may have renal involvement because of isolated diabetic nephropathy (DN), isolated non-diabetic renal disease (NDRD), or mixed lesions (DN combined with NDRD). This study was conducted to find out incidence, histopathological pattern, and clinical predictors of NDRD in the Kashmiri population. This is a single-center prospective observational study conducted from August 2015 to July 2017. Patients with T2DM presenting with atypical clinical features of renal involvement underwent kidney biopsy. A total of 33 patients were included. Isolated NDRD was found in 16/33 (48.5%) patients, isolated DN was discovered in 10/33 (30.3%), and mixed lesions in 7/33 (21.2%) patients. NDRD with or without DN was present in 23/33 (69.7%) patients. Overall, the most common renal histopathological lesion in NDRD was immunoglobulin A (IgA) nephropathy present in 7/23 (30.4%) patients. In mixed lesions, FSGS and TMA were the most common renal lesions present in 2/7 (28.57%) patients. The mean duration of diabetes in NDRD and isolated DN groups was 4.4±3.6 and 7.0±2.9 years, respectively (P = 0.04). NDRD was present in 21/23 (91.3%) patients without diabetic retinopathy (P = 0.016). Our data demonstrated that more than half of the patients with T2DM with atypical features had NDRD upon renal biopsy. The absence of diabetic retinopathy and a shorter duration of diabetes were indicators of NDRD. IgA nephropathy was the most prevalent renal pathology. Clinicians must consider kidney biopsy liberally, especially in patients with unclear etiology of a kidney disease.